2008
DOI: 10.4049/jimmunol.180.10.7028
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Sensitivity of CD22-Specific Chimeric TCR Is Modulated by Target Epitope Distance from the Cell Membrane

Abstract: We have targeted CD22 as a novel tumor-associated Ag for recognition by human CTL genetically modified to express chimeric TCR (cTCR) recognizing this surface molecule. CD22-specific cTCR targeting different epitopes of the CD22 molecule promoted efficient lysis of target cells expressing high levels of CD22 with a maximum lytic potential that appeared to decrease as the distance of the target epitope from the target cell membrane increased. Targeting membrane-distal CD22 epitopes with cTCR+ CTL revealed defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
185
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(196 citation statements)
references
References 60 publications
9
185
1
1
Order By: Relevance
“…Global lymphodepletion has been shown to increase T-cell survival, 16,17 but the effect of selective B-cell lymphodepletion before adoptive transfer of B-cell antigenspecific T cells has not been evaluated. Although several B cellassociated molecules have been targeted by cTCRs, including CD19, 18,19 CD20, [1][2][3] and CD22, 5 no studies have addressed the in vivo function of cTCR ϩ T cells in a model system in which both normal and neoplastic cells express the same target molecule. In this study we have targeted CD20 on both normal and leukemic B cells in immunocompetent mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global lymphodepletion has been shown to increase T-cell survival, 16,17 but the effect of selective B-cell lymphodepletion before adoptive transfer of B-cell antigenspecific T cells has not been evaluated. Although several B cellassociated molecules have been targeted by cTCRs, including CD19, 18,19 CD20, [1][2][3] and CD22, 5 no studies have addressed the in vivo function of cTCR ϩ T cells in a model system in which both normal and neoplastic cells express the same target molecule. In this study we have targeted CD20 on both normal and leukemic B cells in immunocompetent mice.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In vitro experimentation has shown that high expression density of CD20 on normal human B cells down-modulates cTCR molecules from the surface of CD20-specific cTCR ϩ T cells. 5 Downmodulation of canonical TCR has been associated with reduced sensitivity and effector functions, 6 suggesting cTCR downmodulation may limit target recognition. Persistent exposure to CD20 on B cells may also impair CD20-specific cTCR ϩ T-cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…tumor cells [38], and CAR-mediated targeting of an epitope of CD22 located in close proximity to the tumor cell membrane was more efficient than targeting a more distally located epitope [39]. The density of target molecules on the tumor cell and of CARs on the T cell may also significantly impact CAR-modified T cell function [39,40]. These observations highlight the fact that CAR design is in evolution, and it is presently unclear if there are cardinal characteristics of CAR design that are necessary for optimal clinical efficacy of CAR-modified T cells.…”
Section: Design Of Chimeric Antigen Receptorsmentioning
confidence: 99%
“…For example, a ROR1-specific CAR incorporating a short extracellular spacer between the scFv and transmembrane domain was more effective than its long spacer counterpart in lysis of ROR1 ? tumor cells [38], and CAR-mediated targeting of an epitope of CD22 located in close proximity to the tumor cell membrane was more efficient than targeting a more distally located epitope [39]. The density of target molecules on the tumor cell and of CARs on the T cell may also significantly impact CAR-modified T cell function [39,40].…”
Section: Design Of Chimeric Antigen Receptorsmentioning
confidence: 99%
“…Other CARtargeting CD22 (CART22), CD23 (CART23), and CD70 (CART70) antigens as well as κ LC (CARTκ) were also developed showing promising results in in vitro and in vivo mouse tumour models. [57][58][59][60] With respect to the therapeutic potential of tested CAR, it is worthwhile to note that suboptimal cytotoxic effects of these genetically engineered T cells vary among targeted antigens. Although several explanations may be proposed, one possible reason is the difference in expression levels of the targeted antigens in malignant and normal B cells.…”
Section: Cd80 Antigenmentioning
confidence: 99%